147 Cranial Nerve Metastasis Treated with Stereotactic Radiosurgery: A Single Institution Experience. (1st April 2022) - Shahsavari, Nastaran; Ahmad, Maleeha; Ding, Victoria; Pollom, Erqi; Han, Summer; Soltys, Scott G.; Chang, Steven D.; Meola, Antonio
Abstract : INTRODUCTION: Cranial nerves are rarely affected in patients with solid, extra-axial malignant tumors. Involvement of the cranial nerves can severely impact the patient's symptoms and quality of life. Cancer invasion of cranial nerves typically occurs either as leptomeningeal disease (LMD) by CSF spread or as direct spread (DS) from the primary and metastatic head and neck tumors. METHODS: All patients with cranial nerve metastases treated with SRS at our institution between April 2003 and February 2021 were retrospectively identified from electronic health records. Clinical assessment and magnetic resonance imaging (MRI) were performed pre-SRS, and 1 to 3 months post-SRS. Kaplan-Meier estimator was used for evaluating overall and progression-free survival (OS and PFS) at 6 months and the log-rank test was applied to compare survival by each disease subgroup. RESULTS: Our study cohort consisted of 17 patients including 8 LMD and 9 DS patients. The median age was 60.9 years at initial SRS. In total, 30 cranial nerve metastases were treated with SRS. The median duration of follow-up was 17 months. Among 13 pre-SRS symptomatic patients, symptoms improved in 5 patients (38.4%), remained unchanged in 7 patients (53.8%), and worsened in one patient (7.6%). Local tumor control was achieved in 12 patients (70.6%). Three patients died within 6 months of the initial SRS date, all of whom belonged to the LMD group. Overall survival at 6 months was 82.4% for the entire cohort, with 62.5% and 100% for the LMD and DS subgroups, respectively (P = 0.048). There was insufficient evidence to suggest a difference in progression-free survival between subgroups (p = 0.198). CONCLUSION: Our study shows that SRS may be an effective treatment for cranial nerve metastasis providing 70.6% local tumor control, and clinical stability or improvement in over 92% of symptomatic cases.